1985
DOI: 10.1093/nar/13.24.8913
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequencing and expression of subtilisin Carlsberg fromBacillus licheniformis

Abstract: The gene encoding subtilisin Carlsberg from Bacillus licheniformis has been isolated by molecular cloning using a mixture of synthetic oligonucleotides. The entire nucleotide sequence of the coding sequence as well as 5' and 3' flanking sequences have been determined. The deduced amino acid sequence reveals an N-terminal signal peptide consisting of 29 residues, a pro-peptide of 76 residues followed by the mature protein comprising 274 residues. The ATG initiator codon is preceded by two putative overlapping r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
2

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(100 citation statements)
references
References 29 publications
2
96
0
2
Order By: Relevance
“…Conserved Domain Database analysis (NCBI) showed that the predicted protein belonged to the subtilase family (family S8) of serine proteinases. Catalytic triad analysis showed that it contained identical catalytic residues, i.e., Asp138, His 169 and Ser 323, to subtilisin Carlsberg from Bacillus lechiniformis (Jacobs et al 1985). These results indicated that we have cloned a serine proteinase and not the aminopeptidase gene from Grifola frondosa.…”
Section: Discussionmentioning
confidence: 79%
“…Conserved Domain Database analysis (NCBI) showed that the predicted protein belonged to the subtilase family (family S8) of serine proteinases. Catalytic triad analysis showed that it contained identical catalytic residues, i.e., Asp138, His 169 and Ser 323, to subtilisin Carlsberg from Bacillus lechiniformis (Jacobs et al 1985). These results indicated that we have cloned a serine proteinase and not the aminopeptidase gene from Grifola frondosa.…”
Section: Discussionmentioning
confidence: 79%
“…They are numbered according to that of SBPN as is conventional, and are given in full to clear up some confusions from the published sequence data and the coordinates in the Brookhaven Protein Data Bank. The sequences given for BI168 (Stahl & Ferrari, 1984), SBAS (Yoshimoto et al, 1988), SBPN (Wells, Ferrari, Henner, Estell &Chen, 1983;Vasantha, Thompson, Rhodes, Banner, Nagle & Filpula, 1984) and SBCARL (Jacobs, Eliasson, Uhlen & Flock, 1985) are those for the corresponding genes. These differ somewhat from those reported for direct sequencing of the protein for SBAS (Kurihara et al, 1972), SBPN (Markland & Smith, 1967) and SBCARL (Smith et al, 1968); the direct sequence has not been published for SBI168.…”
Section: Homology In the Bacilli Subtilisinsmentioning
confidence: 99%
“…The subtilisin genes from four Bacillus species have been cloned, sequenced and expressed in Bacillus * Present address: Hoechst AG, D-6000 Frankfurt/M, Germany Offprint requests to: J. Kreft subtilis (reviewed in Wells et al 1987 a). Among these were the genes for subtilisin Carlsberg from B. licheniformis (Jacobs et al 1985;Berger et al 1987) and for subtilisin BPN' from B. amyloliquefaciens (Wells et al 1983;Vasantha et al 1984). Many attempts have been made to modify the enzymatic properties of subtilisins, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The alkaline exoproteases from B. amyloliquefaciens (Wells et al 1983;Vasantha et al 1984), B. subtilis (Stahl and Ferrari 1984) and B. licheniformis (Jacobs et al 1985;Berger et al 1987) are translated, like bacillar neutral protease, as preprosubtilisins, which contain a large prosequence between the presumptive signal (pre-) sequence and the mature part of the enzyme. There has been some controversy about the course of preprosubtilisin processing; we therefore undertook a search for processing intermediates of subtilisin Carlsberg produced from the cloned wild-type gene in B. subtilis.…”
Section: Introductionmentioning
confidence: 99%